Adult height and risk of gastric cancer: a pooled analysis within the Stomach cancer Pooling Project. Issue 3 (10th May 2023) - Giraldi, Luca; Stojanovic, Jovana; Arzani, Dario; Persiani, Roberto; Hu, Jinfu; Johnson, Kenneth C.; Zhang, Zuo-Feng; Ferraroni, Monica; Palli, Domenico; Yu, Guo-Pei; La Vecchia, Carlo; Pelucchi, Claudio; et al.
Abstract : Background: The association between height and risk of gastric cancer has been studied in several epidemiological studies with contrasting results. The aim of this study is to examine the association between adult height and gastric cancer within a large pooled analysis of case-control studies members of the Stomach cancer Pooling (StoP) Project consortium. Methods: Data from 18 studies members of the StoP consortium were collected and analyzed. A multivariable logistic regression model was used to estimate the study-specific odds ratios (ORs) and 95% confidence intervals (CIs) for the association between 10-cm increase in height and risk of gastric cancer. Age, sex, tobacco smoking, alcohol consumption, social class, geographical area and Helicobacter pylori (H. pylori ) status were included in the regression model. Resulting estimates were then pooled with random-effect model. Analyses were conducted overall and in strata of selected variables. Results: A total of 7562 cases and 19 033 controls were included in the analysis. The pooled OR was 0.96 (95% CI 0.87–1.05). A sensitivity analysis was performed restricting the results to the studies with information on H. pylori status, resulting in an OR of 0.97 (95% CI 0.79–1.20). Conclusion: Our study does not support a strong and consistent association between adult height and gastric cancer.